PERAN PUSTAKAWAN DALAM UPAYA PROMOSI PEMANFAATAN PERPUSTAKAAN DI BADAN PERPUSTAKAAN DAN ARSIP DAERAH KABUPATEN MANGGARAI - Pantur, Angelda Lastriyanti; Ginting, Richard Togaranta; Kastawa, Made (Jurnal Ilmiah Ilmu Perpustakaan dan Informasi, 2016)
ABSTRACT This research aims to show the role of librarian on library usage promotion Public Library and Archives Board of Manggarai Regency. This research uses descriptive quantitative method. The Techniques of collection data  are observation, questionnaire and literature study. The data was taken based on the results of the questionnaire. The data analysis used quantitative methods by calculating the amount of the data collected and presenting data in formulas and then describe it. The results of this reserach is the role of librarians on the library usage promotion shows that the librarians have done library usage promotion periodically (once on 3 months), especially promotion which held in any school by effective communication to library visitor or library user at Manggarai Regency. This program is  expected can increase the visitation of user and the users can feel satisfied when they come to library. Keyword :Librarian, Library Promotion, Library Usage, Library Usage Promotion